Effects of High Ammonium Loading on Two Submersed Macrophytes of Different Growth Form Based on an 18-Month Pond Experiment - Yu, Qing; Wang, Haijun; Wang, Hongzhu; Xu, Chao; Liu, Miao; Ma, Yu; Li, Yan; Ma, Shuonan; Hamilton, David P.; Jeppesen, Erik (Frontiers in Plant Science, 2022)
Ammonium (NH4-N) produces a paradoxical effect on submersed macrophytes because it is not only the preferred nitrogen source for the growth of plants but also threatens the growth of plants at high concentration. Whether short-term and small-scale physiological toxicity experiments at an individual level can reflect the effects of high ammonium on populations of submersed macrophytes in natural conditions is still unclear. In this study, an 18-month experiment was conducted in six 600 m2 ponds subjected to different levels of ammonium loading. The effects of high ammonium on populations of canopy-forming Myriophyllum spicatum and rosette-forming Vallisneria natans were explored. The results showed that M. spicatum and V. natans populations can develop high cover and height at high ammonium concentration (7 mg/L) at short-term exposures, and V. natans may be tolerant to 18 mg/L ammonium concentration. However, the cover of M. spicatum and the height of both species were inhibited at 2.4 mg/L at long-term exposures. The height of M. spicatum was two to six times higher than that of V. natans across all treatments and control by the end of the experiment, and the cover of M. spicatum was 7–11 times higher than that of V. natans in most NH4-N loading treatments, except the cover of M. spicatum in the highest NH4-N loading treatment with 18 mg/L NH4-N. The rosette-forming V. natans resists ammonium stress by slow growth (shoot elongation) to reduce consumption, while canopy-forming species resist ammonium stress by shoot elongation and canopy development to capture light. Although increasing ammonium concentration may induce severe stress on M. spicatum, the morphological characteristics of this species may, to some extent, release the plants from this stress. Our present study indicates that the negative effects of ammonium stress on the development of populations increased with exposure duration, and the submersed macrophyte community with stronger ability for light capture and dispersal may resist high ammonium stress. Nevertheless, in strongly ammonium-enriched systems, competition and succession cannot be neglected.